Aspirin's Antiplatelet Effects Promote Arteriovenous Fistula Maturation in Hemodialysis Patients: A Systematic Review - Bunga, Febrianto Elivas Haba; Jessica Nadia Dinda; Evelyne Naftali Halim; Maikel Triyudi Tappang (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Arteriovenous fistula (AVF) is the preferred vascular access for hemodialysis, offering superior long-term patency and lower infection rates compared to other options. However, AVF maturation remains a significant challenge. This systematic review aims to evaluate the efficacy of aspirin in promoting AVF maturation and preventing failure in hemodialysis patients. Methods: A comprehensive search of electronic databases, including ScienceDirect, SpringerLink, PubMed, Cochrane, and ProQuest, was conducted from 2014 to 2024. Studies investigating the impact of aspirin on AVF maturation and failure were included. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. Results: Five studies met the inclusion criteria, encompassing a total of 982 participants. Four studies indicated that aspirin significantly enhanced AVF maturation by increasing flow volume and promoting the development of a robust fistula. However, one study found that aspirin did not significantly reduce the risk of thrombosis or AVF failure. Conclusion: Aspirin appears to be a promising adjunct therapy for promoting AVF maturation in hemodialysis patients. Its antiplatelet effects, primarily through cyclooxygenase inhibition and reduced platelet activation, contribute to improved flow volume and fistula maturation. While the evidence for aspirin's role in preventing AVF failure is mixed, its potential benefits in enhancing maturation warrant further investigation.